Uniform Price Market and Behaviour Pattern: What Does the Iberian Electricity Market Point Out? - Marques, Vítor (2008)
The electricity spot markets can be considered as capacity constrained markets (Kreps and Scheinkman, 1983), where market price definition depends on the quantity strategies. In this theoretical framework, the main target of the present paper is to show to what extent a spot market organized like a Uniform Price Auction (UPA) is naturally inclined to develop anti-competitive practices, in particular through quantity strategies. To achieve this objective, multivariable models are defined for each daily demand period of the Iberian electricity market. Each model correlates the hourly market price change and the bid quantities of the two main Iberian producers (Endesa and Iberdrola), for every summer between 2001 and 2004. To apply those models one has to solve the endogeneity problem. This exercise is also useful to highlight any anti-competitive behaviour. Quantities produced by the producers with infra marginal bids should not be endogenous when there is no risk that they will not be dispatched, unless producers have some expectations about the system marginal price. In addition, this kind of endogeneity reinforces the model’s theoretical assumption that change in the system marginal price stems from quantity strategies. The models present some expectable but interesting results. Those results show that even base load units’ bids may depend on expectations about the system marginal price evolution. Those expectations can reflect market strategies. Therefore, in a market where the main companies own base load and peak load units, like the Iberian wholesale electricity market, the UPA is an open window to anti-competitive practices based on quantity strategies, such as the raising of the system marginal price through the capacity withdrawal from base load units.